Life history, uses, trade and management of Diospyros crassiflora Hiern, the ebony tree of the central African forests: a state of knowledge - Deblauwe, V. (Elsevier, 2021)
The Central African forest ebony, Diospyros crassiflora Hiern, is a small tree native to the moist forests of the Congo Basin. Its appealing black heartwood was one of the first products to be exported from the Gulf of Guinea in the 17th century and is today one of the main sources of ebony globally. Like for other ebony species, its commercial exploitation raises serious questions about the long-term sustainability of its trade and the viability of its populations, but the dots are yet to be joined. An examination of the interface between biology, trade, and ecology is crucial to identify the interrelated factors that could influence the potential success of its conservation. This paper reviews scientific and grey literature, forest inventories, herbarium and trade data to provide a critical assessment of the main threats to D. crassiflora populations and gaps in the current state of knowledge. It is shown here that the species is widespread but never abundant. In the longer term the species is threatened by forest conversion to agriculture and widespread hunting of large mammals on which the species rely for seed dispersal. It is currently selectively logged principally to make musical instruments and for the hongmu Chinese market, for which only one alternative black wood, the near-threatened Dalbergia melanoxylon Guill. et Perr., is commercially available. Trade statistics suggest that exports from source countries where the species is cut under the forest concession system are relatively low compared to countries like Cameroon which has seen a recent increase in exports, and where ebony is exploited without forest management plans. Logging remains a concern where the exploitation and trade of D. crassiflora are managed in response to demand rather than informed by current stock levels, growth rate and the particular reproductive biology of this species. The recent successes of private sector initiatives to ensure the long-term supply of ebony in Cameroon are promising, but would require long-term and large-scale commitments involving direct and indirect stakeholders to develop programs for the plantation and policies for the sustainable management of the species.